New (sub)urbanism? - How German cities try to create “urban” neighborhoods in their outskirts as a contribution to solving their recent housing crises - Uwe Altrock (Urban Governance, 2022)
The paper explains the current state of greenfield development for housing in major German cities. The respective projects are a result of the ways metro regions are structured both administratively and physically, the resulting governance arena that is dominated by the core cities but characterized by a number of constraints that make large greenfield developments increasingly difficult, and the complex socioeconomic and cultural realities in relatively “mature” post-industrial urban environments. The paper demonstrates that the resulting development model builds on an attempt to realize “urban” features and qualities in the periphery. It seeks to meet the changing demand for housing and to respond to multiple sustainability requirements. In this respect, it differs significantly from “modernist” suburban development in the 20th century both in terms of physical structures and the roles of the participating stakeholders.For this purpose, the paper analyzes the governance arenas surrounding important greenfield projects that are currently developed. It shows how contested decision making is in a complex environment of contradicting claims to urban planning and housing policies, and that the new neighborhoods can neither be seen as mere appendices of existing peripheral settlements, nor will they ever be able to act as autonomous “new towns”. The planning and implementation efforts depend on the ability of the core cities of metro areas to coordinate fragmented governance arenas, to mobilize supporters and to overcome tenacious resistance from a loose coalition of opponents to peripheral development.